(untitled) (Eurasian Medical Research Periodical, 2023)
Observations were made to study actual nutrition and an attempt to rationalize it using the example of students aged 11-13 and 14-17 years old in the winter-spring period of rural secondary schools located in the Karshi destrict of the Kashkadarya region of the Republic of Uzbekistan. The results obtained indicate that in the diet of students of the first group, total protein averages 71.2±1.6 g, the second - 73.3±1.8 g, against the physiological norm of 86 and 94 g, respectively. In order to improve nutrition, propaganda work was carried out in the form of optional lessons with students, conversations with their parents and seminars with teachers on the rational nutrition of children. As a result, the total protein in the diet of the subjects increased to an average of 77.4±1.9 g in the first group and 80.5±1.6 g in the second. In addition, positive changes were also observed regarding individual mineral elements (Ca) and vitamins B2 and C